2018
DOI: 10.1242/jeb.187989
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaDNA/RNA methyltransferase contributes to robust host defense in ageing animals by regulating sphingolipid metabolism

Abstract: Drosophila methyltransferase (Mt2) has been implicated in methylation of both DNA and tRNA. In this study, we demonstrate that loss of Mt2 activity leads to an age dependent decline of immune function in the adult fly. A newly eclosed adult has mild immune defects that exacerbate in a fifteen-day old Mt2-/- fly. The age dependent effects appear to be systemic, including disturbances in lipid metabolism, changes in cell shape of hemocytes and significant fold changes in levels of transcripts related to host def… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 88 publications
(106 reference statements)
0
17
0
Order By: Relevance
“…Hence, it can be postulated that a novel methyltransferase might be working closely with Dnmt2 to establish the methylation pattern observed in wild-type flies. Dnmt2 mutant flies were shown to be susceptible temperature, oxidative and viral stress 16,17,29 ; additionally, the ability to handle bacterial infection in these flies is reported to reduce in an age dependent manner accompanied by changes in hemocyte shape and lipid profile 18 . In the light of the presented data, further analysis of the DNA methylation in the adult Dnmt2 mutant flies might reveal its role in handling biotic or abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it can be postulated that a novel methyltransferase might be working closely with Dnmt2 to establish the methylation pattern observed in wild-type flies. Dnmt2 mutant flies were shown to be susceptible temperature, oxidative and viral stress 16,17,29 ; additionally, the ability to handle bacterial infection in these flies is reported to reduce in an age dependent manner accompanied by changes in hemocyte shape and lipid profile 18 . In the light of the presented data, further analysis of the DNA methylation in the adult Dnmt2 mutant flies might reveal its role in handling biotic or abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The dDNMT2 gene has been implied to be involved in the regulation of stress and immune response 1517 . Involvement of Mt2 in contributing to Drosophila immunity against bacterial infection in an age-dependent manner accompanied by changes in the sphingolipid metabolism has been demonstrated 18 . The embryos of DNMT2 knockout flies have shown the persistence of DNA methylation albeit with an altered pattern clearly indicating a possibility of existence an unknown DNA methyltransferase in Drosophila 5 .…”
Section: Introductionmentioning
confidence: 99%
“…During the stress response, Dnmt2 appears to control the fragmentation of tRNA and can be located at cellular stress compartments 15,51 . More recently, it has also been demonstrated that the knockout of Dnmt2 leads to a decline of immune function with ageing in adult flies 52 . Finally, its absence disrupts the small interfering RNA pathway by inhibiting dsRNA degradation by Dicer 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to wild-type rats, Hcy-stimulated NSun2(-/-) rats showed significantly reduced levels of ICAM-1 and leucocyte adhesion to endothelial cells. 76 Specifically, Dnmt2(-/-) flies presented an age-dependent decrease in sphingosine-1-phosphate (S1P) lyase activity and concomitant accumulation of S1P, which in turn led to age-dependent damage to anti-infective capacity. Analogously, NSun2 methylated the IL-17A mRNA in an m5C pattern to promote the translation of IL-17A in T lymphocytes, thereby mediating the chronic inflammation caused by plasma Hcy.…”
Section: Trna Modifications and Immune Responsesmentioning
confidence: 99%
“…75 New studies confirmed that defects in Drosophila Dnmt2 reduced immune function with age by affecting sphingolipid metabolism. 76 Specifically, Dnmt2(-/-) flies presented an age-dependent decrease in sphingosine-1-phosphate (S1P) lyase activity and concomitant accumulation of S1P, which in turn led to age-dependent damage to anti-infective capacity. Mechanistically, Dnmt2 might regulate the genetic loci of S1P lyase, so that ageing animals still had a strong host defence against pathogens.…”
Section: Trna Modifications and Immune Responsesmentioning
confidence: 99%